Consumer Intention towards the Use of Bible Application - Opoku, Daniel; Okyireh, Rexford Owusu; Kissi, Philip Siaw (American Journal of Education and Learning, 2020)
The study sort to examine the factors that influence users’ attitude towards bible application adoption from the Ghanaian perspective. The study used 300 sample size and a purposive technique to solicit views from respondents. Questionnaires were used to elicit information from respondents. Data analysis was performed using SPSS and SmartPLS application. The study reports that perceived usefulness is not statistically significant in influencing attitude to learn using bible application on mobile devices. Contrary to this, perceived ease of use, social influence and application content have a significant influence on the attitude of bible users. The study, therefore, contributes to the research gap on the lack of mobile application studies in developing countries that have emphasized the use of mobile apps. Efforts must be made to conduct the study in different geographical contexts as well as the usage of a mix method approach to understand the reasons that make people to either adopt or reject innovation.